Mulheres e água: perspectivas, desigualdades de gênero e gestão sustentável dos recursos hídricos - Sousa, Fernanda Vale de (Universidade Federal de São Carlos, 2023)
Water is a fundamental resource in environmental, ecological, economic, and political terms, and as its demand has increased, the human relationship with water has shifted to a purely utilitarian view. However, it is possible to go beyond the associations between man and water, which include social and cultural links that have been forgotten, among which the relationship between women and water is present but still little valued. There are notable gender asymmetries in control, access, and use of resources, as well as greater male participation in public and decision-making positions in water management. Given the important role that women play in water management and conservation, it was necessary to look at their relationships and women's perceptions of water, questioning the inequalities related to water resources in Brazil. Therefore, this research aimed to explore, identify, and analyze women's different relationships with rivers and springs, as well as women's perspectives on better water management and conservation. To this end, a systematic bibliographic review was conducted, as well as case studies with 12 female protagonists involved with water, rivers, and springs, through the application of interviews, and the content analysis method was used to analyze the results. The results showed that women have different knowledge and valuable visions related to water for the management and conservation of this resource. These varieties refer to the context in which the protagonists are situated, as well as their life experiences and the direct nature of their relationship with water. However, the current scenario still shows a discrepancy in the unequal participation of women in the management of water resources, in different areas, contexts, levels of control, and access, when it comes to the relationship that both genders have with water. Incorporating a gender perspective aims to include the participation and empowerment of women in all stages of decision-making, with a view to alternatives to reduce these asymmetries. The aim is to achieve greater involvement of women (contributing to social balance) in water management and conservation processes, enabling and promoting gender equality and its relationship with water management.
Women and water: perspectives, gender inequalities, and sustainable management of water resource
Keywords: Políticas públicas; Percepção; Protagonismo feminino; Public politics; Perception; Female protagonism; ENGENHARIAS::ENGENHARIA SANITARIA::RECURSOS HIDRICOS::PLANEJAMENTO INTEGRADO DOS RECURSOS HIDRICOS